Model-driven design of a fast material removal electrical discharge machine. Issue 1 (31st December 2016) - Hu, Bo; Mo, John P.T.; Ding, Songlin; Brandt, Milan
Abstract: In order to minimize cost of machining, modern aerospace components are highly unitized to utilize functions of multi-axes CNC machining centres. However, PCD tools are preferred for machining of titanium alloys and metal matrix composites but they are hard to grind. A new fast material removal electric discharge machine suitable for small PCD workpiece machining has been developed from an innovative model consisting both high and low frequency response actuators and a dual stage non-linear control algorithm. This innovative approach has been proved successful in the single axis machine prototype and the fast material removal rate has been verified a series of tests and the outcomes were verified.